El Oriente: The afternoon newspaper [Oct 1934] - Eliseo Salazar (My University, 1934)
Diario regional independiente; informativo; de publicidad comercial, galardonado con diploma de honor en 1923 y diploma y medalla de oro en 1924 por la municipalidad de Iquitos; octubre de 1934

Independent daily regional newspaper; informative; commercial publicity, awarded a diploma of honor in 1923 and a diploma and gold medal in 1924 by the municipality of Iquitos; october 1934
El Oriente: El diario de la tarde [Oct 1934]
Keywords: Publicity; Politics and government; Commerce; Health and medicine; Accounting and finance; Arts; Sports and recreation; Nationality heros; Military; Education